Stepping dynamics of the bacterial flagellar motor and F1-ATPase - Nord, A (2014)
Rotary molecular motors are protein complexes which convert chemical or electrochemical energy from the environment into mechanical work in the form of rotary motion. The work in this thesis examines two of these motors: the F1 portion of F1FO- ATP synthase, which is responsible for ATP production in bacteria and eukaryotes, and the bacterial flagellar motor (BFM), which rotates the flagella of a bacterium, enabling locomotion. The aim of these investigations was to measure the stepping dynamics of these motors, in order to further elucidate details of the stepping mechanism, the mechanism of rotation, and the mechanochemical cycle. A back-scattering laser dark field microscope of unprecedented resolution was designed and constructed to observe the rotation of gold nanoparticles attached to fixed motors. This micro- scope is capable of sub-nanometer and 20μs resolution. The protocols and algorithms to collect and analyze high resolution rotational data developed for these experiments have yielded novel discoveries for both F1 and the BFM. While most of the previous single-molecule work has been done on F1 from the thermophilic Bacilus PS3 (TF1), only mitochondrial F1 has been well characterized by high-resolution crystal structures, and single-molecule studies of mesophilic F1 are lacking. This thesis presents evidence that mesophilic F1 from E. coli and wild type yeast F1 from S. cerevisiae are governed by the same mechanism as TF1 under laboratory conditions. Experiments with yeast F1 mutants allow a direct comparison between single-molecule rotation studies and high resolution crystal structures. A data set of unprecedented size and resolution was acquired of high speed, low load BFM rotation, enabling the first observation of steps in the BFM under physiological conditions. Preliminary results from this analysis question previously published results of the dependence of speed on stator number at low load and provide novel hypotheses necessitating new models of BFM rotation.